SEBARAN POPULASI PULAI (ALSTONIA SCHOLARIS) DI KAWASAN HUTAN KOTA GUNUNG SARI SINGKAWANG - Dilan, Tubel Agustinus; Ekyastuti, Wiwik; Muflihati, . (Universitas Tanjungpura, 2016)
Indonesia as a tropical country has a fairly extensive natural forest with various types and natural conditions, as well as a fairly considerable species diversity . Such conditions provide an ideal habitat for the growth of a variety of flora and fauna . Indonesiaâ€™s forest are being exploited on an extensive scale, many trees with high economic values have been cut down or cleared for plantations, both for domestic needs and developed further, as only a small portion of it is managed i.e. the infrastructure . The Gunung Sari urban forest has a lot of potential that needs to be explored and untilized, one of which is the pulai (Alstonia scholaris) . Therefore, it is necessary to condust research to findÂ out the distribution pulai (Alstonia scholaris) population in the area of the Gunung Sari urban forest of Singkawang city . This study aimed to find out the distribution the Pulai (Alstonia scholaris) population found in the Gunung Sari urban forest of Singkawang, West Kalimantan . The method used in the this research was the line plot technique which is a combination of transect and double plots . The results of observations indicated the pulai plant that grew in the area of the Gunung Sari urban forest of Singkawang had a clustered distribution patterns for all levels growth (seedling, sapling , pole and tree). Keyword : Gunung Sari urban forest, pulai distribution